2014
DOI: 10.1155/2014/519197
|View full text |Cite
|
Sign up to set email alerts
|

Canine Oral Eosinophilic Granuloma Treated with Electrochemotherapy

Abstract: A case of a canine oral eosinophilic granuloma in a 14-year-old female crossbred is described. The dog was presented with a history of ptyalism, halitosis, local pain, decreased appetite, and blood staining noted on food and water bowls. Clinical, hematologic, and biochemical examinations, abdominal ultrasonography, and 3-view chest radiographs were performed, and no metastases were found. Histopathologic examination of two 6 mm punch biopsies from the oral lesion revealed the presence of eosinophilic granulom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…The relative permeabilized tissue conductivity (r MAX /r 0 ) was 3.5. This value is compatible with muscle (2.5-5 (11)(12)(13)(14)), connective tissues (3 (30)), and dermis (4 (16)) electroporation experiments. The threshold electric field values (E rev 5 20 kV/m and E irrev 5 80 kV/m) are similar to muscle electroporation models (12,13).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The relative permeabilized tissue conductivity (r MAX /r 0 ) was 3.5. This value is compatible with muscle (2.5-5 (11)(12)(13)(14)), connective tissues (3 (30)), and dermis (4 (16)) electroporation experiments. The threshold electric field values (E rev 5 20 kV/m and E irrev 5 80 kV/m) are similar to muscle electroporation models (12,13).…”
Section: Discussionsupporting
confidence: 76%
“…The intensity of applied electric field will be higher than necessary, and this EQT may produce tissue damage. The electroporation models present tissue electric conductivity dependent on local electric field (11)(12)(13)(14)18).…”
mentioning
confidence: 99%
“…The majority of reported cases have used corticosteroid monotherapy to achieve successful control. With large CEG lesions, surgical debulking has been performed . Glucocorticoids may be combined with oral azathioprine for refractory cases .…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids may be combined with oral azathioprine for refractory cases . Reported treatments for CEG may also include chlorpheniramine and electrochemotherapy with bleomycin . To the best of the authors' knowledge, chlorambucil or laser ablation for dogs with EG has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America, several research projects on electroporation-based treatments started in the last decade, both to elucidate their fundamental aspects and to extend their applications. In particular, the group of Dr. Marshall made several publications on this topic [ 10 , 70 , 97 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. The use of ECT in veterinary medicine began in 2008 in Brazil by the group of Dr. Rangel [ 109 , 110 , 111 , 112 , 113 , 114 ], closely followed by the group of Dr. Marshall, from Argentina, in 2009.…”
Section: State Of the Art Of Electroporation-based Treatments In Lmentioning
confidence: 99%